Guidelines for gender-responsive seed systems development - Bomuhangi, Allan; Yila, Jummai; Puskur, Ranjitha; Khan, Afreen (International Rice Research Institute, 2025)
Developing seed systems that work for everyone is important for food security, climate adaptation, and agricultural development. As this guideline has presented, achieving this requires a deliberate and systemic shift from gender-blind approaches to those that are genuinely gender-responsive. The persistent exclusion of women from key seed sector functions, ranging from varietal development and production to distribution and governance, comes at a high cost, resulting in lower productivity, weakened resilience, and forgone economic gains. The evidence and actions presented here demonstrate that change is possible. Through reorienting seed sector ambitions and designing gender-responsive interventions, the specific barriers women face can be addressed. This means moving beyond simply ensuring women have access to seed. It requires actively supporting their roles as seed entrepreneurs, ensuring their trait preferences shape breeding programs, tailoring services to their needs, and guaranteeing they have a voice in the policies and organizations that govern the seed sector. The successful examples from Syria, Burkina Faso, India, Uganda, and elsewhere prove that when space is intentionally created for women's knowledge and leadership, the entire system benefits. Operationalizing this change rests on foundational principles: dismantling structural barriers, using an intersectional lens, integrating interventions across all seed functions, and shifting the focus from women's access to their agency and control. Supporting this, a robust monitoring and evaluation framework is crucial for tracking progress, ensuring accountability, and continuously learning from experience. Transforming seed systems is thus not just a technical challenge; it is a social and economic imperative. Gender-responsive seed systems are not optional.  Embedding gender analysis into every function of the seed sector is a practical pathway to building seed systems that are not only more equitable but also more effective, efficient, and sustainable. “When seed systems work for women, they work better for everyone.”